0394 Do Patients Change TIB When Starting Hypnotics and Does This Affect Outcomes?. (12th April 2019) - Bremer, Erin; Morales, Knashawn; Vargas, Ivan; Grandner, Michael; Ellis, Jason; Posner, Donn; Kloss, Jackie; Perlis, Michael L
Abstract: Introduction: Given that the regulation of time in bed (TIB) is a key component of CBT-I, this naturally leads to the question, "do patients change TIB when starting hypnotics and does this affect outcomes?". Methods: As part of a study on partial reinforcement, 108 subjects with Chronic Insomnia were monitored for two weeks prior to medication use and then for one month when prescribed 10mg/qhs of zolpidem. Monitoring was accomplished with online daily sleep diaries. Subjects were typed based on whether they restricted (R-TIB > 30 min), maintained (M-TIB +/-30), or increased (I-TIB > 30 min) their TIB. These groups were then compared for differences in treatment response (% treatment responders). Results: 14% restricted (R-TIB), 48% maintained (M-TIB), and 38% increased (I-TIB) TIB. Preliminary analyses suggest that treatment response did not vary by category (R-TIB [86%], M-TIB [67%], and I-TIB [78%]). As would be expected, the groups significantly differed with respect to TIB (-43 min., -1 min, +60 min for R-TIB, M-TIB, I-TIB respectively). Conclusion: Subjects clearly vary TIB in response medication use. While such behavior does not appear to affect treatment outcome, it may affect the speed with which clinical responses occur. Additional efficacy outcome analyses and treatment response latencies analyses are on-going. Support (If Any): R01AG041783; K24AG055602; R01AT003332